Income distribution and macroeconomics revisited: The role of fertility adjustment - Masao Nakagawa; Yoshiaki Sugimoto (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper develops a theory in which households prepare for future education by adjusting the number of children they intend to raise. Income inequality lowers output per worker only if the inequality is attributed in some part to unexpected disturbances after childbirth.
Keywords: D10; J13; J24; O15; 330; Fertility; Lock-in effect; Inequality; Education; Fertilität; Haushaltseinkommen; Soziale Ungleichheit; Einkommensverteilung; Familienplanung; Privater Haushalt; Kleine offene Volkswirtschaft; Overlapping Generations; Theorie